The great escape - Phillips, Susan Elizabeth (William Morrow & Co., 2012)
In this hilariously heartwarming sequel to Call Me Irresistible, Lucy Jorik, the daughter of the former president of the U.S., jilts her soon-to-be husband at the altar and makes a run for it on the back of a stranger's motorcycle, finally embarking on the adventure she has been waiting for.